From Ordnungs Politic to Digital Circularity: Governance, Culture and Human Agency in the Transition to Regenerative Business Models - Martin Dahl (Universitas Pancasakti Tegal, 2025)
This article develops a governance–culture–agency framework for the transition from linear to regenerative business models by reinterpreting the ordoliberal principle of Ordnungspolitik for the age of digital circularity. Using an integrative literature review and policy document analysis, the study synthesizes insights from ordoliberal political economy, circular economy scholarship, and management/organizational research. Results show that outcome-oriented, technology-neutral framework rules—eco-design and durability requirements, rights to repair and data-for-repair, eco-modulated extended producer responsibility, product passports, and data portability/interoperability—create the enabling conditions for decentralized innovation while safeguarding competition and the common good. Digital tools (AI, IoT, distributed ledgers) can materially enable circular strategies through sensing, prediction, and traceability, but only when embedded in transparent, auditable, and contestable infrastructures that mitigate rebound effects and platform lock-in. Organizational culture and human agency are decisive: leader mindsets, psychological resilience, incentive redesign, and learning routines translate policy signals and digital capabilities into practice. Higher education institutions accelerate diffusion through interdisciplinary curricula, living labs, and standard-setting support. The contribution is a theoretically grounded and actionable architecture that aligns institutional order, technological design, and human development to achieve durable, regenerative outcomes.